Bile acids and microbiota: Multifaceted and versatile regulators of the liver–gut axis - Grüner, Niklas; Mattner, Jochen (International Journal of Molecular Sciences, 2021)
After their synthesis from cholesterol in hepatic tissues, bile acids (BAs) are secreted into the intestinal lumen. Most BAs are subsequently re-absorbed in the terminal ileum and are trans-ported back for recycling to the liver. Some of them, however, reach the colon and change their physicochemical properties upon modification by gut bacteria, and vice versa, BAs also shape the composition and function of the intestinal microbiota. This mutual interplay of both BAs and gut microbiota regulates many physiological processes, including the lipid, carbohydrate and energy metabolism of the host. Emerging evidence also implies an important role of this enterohepatic BA circuit in shaping mucosal colonization resistance as well as local and distant immune responses, tissue physiology and carcinogenesis. Subsequently, disrupted interactions of gut bacteria and BAs are associated with many disorders as diverse as Clostridioides difficile or Salmonella Typhimurium infection, inflammatory bowel disease, type 1 diabetes, asthma, metabolic syndrome, obesity, Par-kinson’s disease, schizophrenia and epilepsy. As we cannot address all of these interesting under-lying pathophysiologic mechanisms here, we summarize the current knowledge about the physio-logic and pathogenic interplay of local site microbiota and the enterohepatic BA metabolism using a few selected examples of liver and gut diseases.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Bile acids; Enterohepatic recirculation; Host–microbe interactions; Intestinal microbiota; Microbial metabolism